Shadows of the Bat. Constructions of Good and Evil in the Batman Movies of Tim Burton and Christopher Nolan Shadows of the Bat - Simon Philipp Born (Journal for Religion, Film and Media, 2017)
The superhero narrative is typically premised on the conflict between the hero and the villain, the mythical struggle between good and evil. It therefore promotes a Manichaean worldview where good and evil are clearly distinguishable quantities. This bipolar model is questioned in the Batman movies of Tim Burton and Christopher Nolan. Since his creation in 1939, Batman has blurred the line between black and white unlike any other classic comic book superhero. As a "floating signifier", he symbolizes the permeability of boundaries, for his liminal character inhabits a world between light and darkness, order and anarchy, hero and villain. Drawing on the complex ambiguity of the character, Tim Burton and Christopher Nolan deconstruct the traditional dichotomy of good and evil in the superhero narrative by reversing its polarity and emphasizing the fictionality of it all. Although they differ in style and method, both filmmakers invite us to overcome the Manichaean belief in favor of a more ambivalent and sophisticated viewpoint.